2019
DOI: 10.1186/s13045-019-0758-x
|View full text |Cite
|
Sign up to set email alerts
|

Target selection for CAR-T therapy

Abstract: Chimeric antigen receptor-modified T (CAR-T) cells have achieved significant success in the treatment of several hematological malignancies. However, the translation of the existing achievements into the treatment of other tumors, especially solid tumors, is not smooth. In addition to the optimization of CAR structures, preparation, and clinical protocols, rational selecting and utilizing the targets was more pivotal. In this review, the criteria for target selection and some new strategies for targets utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 60 publications
0
117
0
5
Order By: Relevance
“…Therefore, the application of CD22 CAR-T cells could be a promising treatment strategy. [32][33][34] Alternatively, CAR engineering could be used to enhance the affinity of the scFv activity against tumor cells with low antigen density. It indicates that by altering the affinity of EGFR and/or HER2 CARs, it is possible to recognize as low levels of antigens as expressed on a normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application of CD22 CAR-T cells could be a promising treatment strategy. [32][33][34] Alternatively, CAR engineering could be used to enhance the affinity of the scFv activity against tumor cells with low antigen density. It indicates that by altering the affinity of EGFR and/or HER2 CARs, it is possible to recognize as low levels of antigens as expressed on a normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the adenine base editor reduces PD-1 by changing the glycosylated residue in CAR-T cells, which could be used to augment CAR-T therapy [107]. In terms of the structure of CAR, a PD-1-CD28 fusion receptor is able to switch original inhibitory signals into activation signal and enhance cytokine release, proliferation, and cytotoxicity of CAR-T cells [121].…”
Section: Strategies Focused On the Bm Microenvironmentmentioning
confidence: 99%
“…Furthermore, in a recent genome-wide CRISPR gene-editing study, BCMA was not found among more than 90 genes essential for MM (14). These are properties which do not fit with the description of the "ideal" target for immunotherapy (15,16).…”
Section: Bcma: the Ideal MM Car Target?mentioning
confidence: 92%